Compromise on the Board: Investigating the Antecedents and Consequences of Lead Independent Director Appointment - Krause, Ryan; Withers, Michael C.; Semadeni, Matthew (Academy of Management Journal, 2017)
Board leadership has always been conceptualized as a tradeoff between two desirable yet mutually exclusive organizational attributes. Classical organization theory prescribes unity of command, achieved by combining the chief executive officer (CEO) and board chair positions; in contrast, agency theory prescribes independent monitoring, achieved by separating the CEO and board chair positions. Extant theory does not acknowledge the possibility that a compromise might exist between these competing theoretical prescriptions, one which might reduce their mutual exclusivity. Such a compromise has emerged in practice, however: the lead independent director. In the present research, we initiate theoretical exploration of this compromise between the prescriptions of agency theory and classical organization theory, addressing the questions of when a board will choose to appoint a lead independent director, who among the independent directors will serve in the position, how lead independent director appointment will impact firm performance, and whether this compromise is a permanent solution or a stepping stone to a more extreme outcome. Analysis of S&P 1500 firms from 2002 to 2012 reveals that lead independent director appointment reflects balanced power on the board, impacts firm performance positively under the right conditions, and generally becomes institutionalized as a permanent governance structure.